Method for preparing advanced oxidation catalyst from waste saggar in lithium battery positive electrode material production process

Through mechanical grinding and acid leaching extraction technology, combined with multiple impregnation and calcination processes, an advanced oxidation catalyst is prepared, which solves the problem of insufficient utilization of waste saggers in the production process of lithium battery cathode materials, and achieves efficient catalysis and comprehensive utilization of resources.

CN119346132AActive Publication Date: 2025-01-24CENT SOUTH UNIV +1

Patent Information

Application Number
CN202411610029.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-24
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The prior art has failed to fully utilize the components in the discarded sachet during the production process of lithium battery positive electrode materials, and only focuses on the recycling of transition metals and lithium, and has failed to achieve comprehensive utilization.

Method used

Ceramic powder is obtained through the surface of the abandoned box, the acid immersion extracts metal ions, and the immersion slag is formed as a carrier particles. After many immersion, drying, and light burning, a high -grade oxidation catalyst is prepared.

Benefits of technology

A comprehensive utilization of transition metal elements and ceramic components in the abandoned box, preparation of high -grade oxidative catalysts that have high -efficiency catalyzed potassium hydrogen sulfate degradation organic pollutants, reducing the treatment cost and increasing resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346132A_ABST
    Figure CN119346132A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing an advanced oxidation catalyst from a waste sagger in the production process of a lithium battery positive electrode material. The method comprises the following steps: mechanically polishing the inner surface of the waste sagger to obtain metal-containing ceramic powder; leaching with acid to obtain an acid leaching solution containing metal ions and leaching residues; concentrating the pickle liquor to obtain concentrated liquor; adding an auxiliary agent into the leaching residue, uniformly mixing, molding, and calcining to obtain a catalyst carrier; putting into a concentration adjusting solution, fully dipping and adsorbing, taking out, drying and lightly burning, and repeating the dipping-drying-lightly burning process to obtain a catalyst precursor; and finally calcining to obtain the catalyst. The method is simple in process, high in feasibility and low in cost, industrial preparation is easy to achieve, comprehensive utilization of transition metal elements and ceramic components in the waste saggar can be fully achieved, and the high-grade oxidation catalyst for efficiently catalyzing potassium peroxymonosulfate to degrade organic pollutants is obtained; the method has important significance on comprehensive and high-value utilization of the waste saggar in the positive electrode material industry and development of an industrial-grade advanced oxidation catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-value utilization of solid waste, and in particular to a method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process. Background Art

[0002] In the production process of lithium battery positive electrode materials such as nickel-cobalt-manganese ternary, lithium cobalt oxide, and lithium manganese oxide, the precursors formed by raw materials such as nickel, cobalt, manganese, and lithium need to be calcined at high temperature to obtain the desired products. The sagger is a container for the precursor. During the calcination process, some precursors will react with the inner wall of the sagger at high temperature in a solid phase, causing metal ions such as nickel, cobalt, manganese, and lithium to diffuse to varying degrees on the inner wall of the sagger. Therefore, when the sagger is discarded, its inner surface will contain different amounts of nickel, cobalt, and manganese transition metal elements. This kind of discarded sagger has the value of resource utilization. For example, Patent ZL201711330025.8 recovers the cobalt and lithium from the discarded sagger produced by lithium cobalt oxide through acid leaching and multi-step impurity removal; Patent ZL201711328413.2 recovers the nickel, cobalt, manganese, and lithium from the discarded sagger produced by ternary positive electrode materials through acid leaching and multi-step slag removal. However, the current resource utilization method for this type of waste sagger is single, focusing only on the recovery of valuable elements such as transition metals and lithium, and failing to fully realize the rational comprehensive utilization of various components in the sagger.

[0003] Granular catalysts loaded with transition metal oxides are very important for the industrial application of advanced oxidation technology, which is conducive to the continuous catalytic degradation of organic wastewater. The preparation method mainly adsorbs transition metal ions on industrial carriers (such as alumina, molecular sieves, etc.) by impregnation, and then converts them into oxides loaded on the surface by high-temperature calcination to form a composite material. At present, there is no report on the preparation of advanced oxidation catalysts using discarded saggers from lithium battery positive electrode production. Summary of the invention

[0004] The present invention provides a method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process, the purpose of which is to solve the above-mentioned problems existing in the background technology.

[0005] In order to achieve the above-mentioned purpose, an embodiment of the present invention provides a method for preparing an advanced oxidation catalyst from waste saggers in the production process of lithium battery positive electrode materials, comprising the following steps: mechanically grinding the inner surface of the waste saggers in the production of positive electrode materials to obtain a ceramic powder containing Co, Mn, and Ni; leaching the ceramic powder with acid to obtain an acid leaching solution and leaching residue containing metal ions such as Co, Mn, and Ni; concentrating the acid leaching solution and appropriately supplementing transition metal salts as needed to obtain a concentrated solution with controllable composition; drying the leached residue, adding an auxiliary agent, mixing evenly and forming it into particles, and then calcining it in a kiln to obtain carrier particles; placing the carrier particles in the concentrated solution for full immersion and adsorption, taking them out, drying them, and lightly calcining them at low temperature, repeating the immersion-drying-lightly calcining process to obtain a catalyst precursor; calcining the catalyst precursor in a kiln to prepare a granular supported advanced oxidation catalyst. The preparation method has simple process, strong feasibility, low cost, and is easy to realize industrial preparation. It can fully realize the comprehensive utilization of transition metal elements and ceramic components in discarded saggers, and obtain advanced oxidation catalysts that can efficiently catalyze potassium permonosulfate to degrade organic pollutants. It is of great significance for the comprehensive and high-value utilization of discarded saggers in the positive electrode material industry and the development of industrial-grade advanced oxidation catalysts.

[0006] An embodiment of the present invention provides a method for preparing an advanced oxidation catalyst from waste saggers in a lithium battery positive electrode material production process, comprising the following steps:

[0007] S1: Mechanically grinding the surface of the waste sagger produced in the production process of lithium battery positive electrode materials to obtain ceramic powder containing transition metals;

[0008] S2: acid leaching the ceramic powder containing transition metals to obtain a leaching solution and leaching residue containing transition metals;

[0009] S3: concentrating the leaching solution containing transition metals to obtain a concentrated solution;

[0010] Wherein, according to the transition metal ion concentration measured in the leachate, the transition metal salt can be appropriately supplemented if necessary; specifically, the leachate containing the transition metal is concentrated, the transition metal ion concentration in the concentrated leachate is measured, and the transition metal ion concentration in the concentrated leachate is supplemented to the target transition metal ion concentration by adding the transition metal salt to obtain a concentrated solution;

[0011] S4: After the leached residue is dried, an auxiliary agent is added, mixed and formed into particles, and then dried and calcined to obtain a catalyst carrier;

[0012] S5: placing the catalyst carrier into the concentrated solution, fully immersing and adsorbing it, taking it out, drying it and calcining it at low temperature, and then placing it into the concentrated solution again, repeating the immersion-drying-calcining process to obtain a catalyst precursor;

[0013] S6: calcining the catalyst precursor to obtain an advanced oxidation catalyst.

[0014] According to one aspect of an embodiment of the present invention, in step S1, the grinding depth of the inner surface of the waste sagger does not exceed 5 mm. It should be noted that while fully realizing the recovery of transition metals, the introduction of ceramic powder is minimized. The ceramic blocks without transition metals remaining after mechanically grinding the inner surface can be crushed and used as machine-made sand or refractory raw materials.

[0015] According to one aspect of an embodiment of the present invention, in step S2, the acid used for acid leaching is sulfuric acid with a mass concentration of 5% to 20%, a leaching liquid-solid ratio of 5:1 to 20:1, a leaching temperature of 20 to 100° C., and a leaching time of 0.5 to 5 h.

[0016] According to one aspect of the embodiment of the present invention, in step S3, the total concentration of transition metal ions in the concentrated solution is 10-100 g / L. Preferably, the concentrated solution can be obtained by appropriately supplementing transition metal salts as needed.

[0017] According to one aspect of the embodiments of the present invention, in step S4, the auxiliary agent is at least one of kaolin, montmorillonite, feldspar, glass powder and fly ash, and the added amount does not exceed 10% of the dry weight of the leached residue.

[0018] According to one aspect of the embodiment of the present invention, in step S4, the molding process includes granulation and extrusion; the calcination temperature is 800-1200° C., and the calcination time is 1-5 hours.

[0019] According to one aspect of an embodiment of the present invention, in step S5, vacuum impregnation is used for 0.5 to 2 hours; the light calcination temperature is 500 to 900° C., and the light calcination time is 0.5 to 3 hours; the impregnation-drying-light calcination process is repeated 2 to 5 times to increase the loading amount of transition metal ions.

[0020] Combined with Comparative Example 1, the impregnation-drying-light calcination process should not be repeated more than 3 times. Too many repetitions will lead to the formation of a dense layer of transition metal oxide on the surface of the carrier, making it impossible for the active components in the inner layer to contact with the peroxymonosulfate, and the catalytic effect will be weakened.

[0021] According to one aspect of the embodiments of the present invention, in step S5, the concentrated solution after the cyclic immersion is completed can be returned to the acid leaching process as a mother solution for use.

[0022] According to one aspect of the embodiment of the present invention, in step S6, the calcination temperature is 600-1300° C., and the calcination time is 1-5 hours.

[0023] Based on a general concept of the invention, an embodiment of the present invention provides the use of the advanced oxidation catalyst prepared by the above method in catalytic degradation of organic matter.

[0024] According to one aspect of an embodiment of the present invention, the advanced oxidation catalyst includes a carrier and an active component coated on the surface of the carrier; wherein the carrier mainly comes from the refractory material in the sagger, and the active component comes from transition metal elements such as nickel, cobalt, and manganese attached to the sagger during the production process.

[0025] According to one aspect of the embodiment of the present invention, the organic matter is a surfactant or a dye, such as sodium dodecylbenzene sulfonate solution, rhodamine B dye, sodium stearate solution, and the like.

[0026] The above scheme of the present invention has the following beneficial effects:

[0027] (1) The technical idea of ​​the present invention breaks through the limitation of the prior art that only the transition metal valuable elements in the sagger are extracted, and realizes the efficient recovery of part of the refractory components of the sagger and all the transition metal elements. The refractory components are used as catalyst carriers, and the transition metal elements are used as catalyst active components, thereby realizing comprehensive utilization.

[0028] (2) The present invention uses mechanical grinding of the inner surface of the waste sagger to obtain refractory powder containing transition metal elements. Compared with the traditional process of crushing the sagger as a whole and then acid leaching it all, this method significantly reduces the introduction of the part of the refractory material that does not contain transition metal elements, significantly reduces the total amount of leached raw materials and increases the content of valuable elements in the leached raw materials, improves the transition metal extraction rate, saves processing costs, and enables the uncrushed sagger part to be crushed into machine-made sand and other comprehensive applications, thereby reducing the volume of solid waste discharged.

[0029] (3) The present invention can fully utilize transition metal elements such as nickel, cobalt, and manganese and common metal elements such as magnesium, aluminum, and calcium in the leachate, and convert them into active components or inert components on the surface of the carrier. Therefore, there is no cumbersome impurity removal process and complex element separation process, and the integrated comprehensive utilization of all metal elements in the leachate is realized simply and efficiently.

[0030] (4) The present invention can achieve regulation of the concentration of each element according to the type and concentration of the elements in the leaching solution by concentrating and additionally supplementing the transition metal salt to meet the composition requirements of the active components; and then by controlling the cyclic impregnation and calcination process, the type and loading amount of the active components on the carrier surface can be flexibly and effectively regulated.

[0031] (5) The present invention can load various types of active components (such as single metal oxides such as cobalt oxide and nickel oxide, and composite metal oxides such as spinel phase and perovskite phase) on the surface of the carrier, thereby obtaining catalysts with different properties, which is beneficial to enhancing the applicability of the catalyst and improving its application performance.

[0032] In summary, the technology and materials for preparing advanced oxidation catalysts from waste saggers produced by lithium battery production of the present invention have multiple advantages in terms of innovation, environmental friendliness, comprehensive utilization, cost-effectiveness, catalytic performance, and later beneficial effects, and have broad application prospects in the resource utilization of solid waste and the application of advanced oxidation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 The present invention is a flow chart of a method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process. DETAILED DESCRIPTION

[0035] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0038] In view of the existing problems, the present invention provides a method for preparing an advanced oxidation catalyst from waste saggers in the production process of lithium battery positive electrode materials, and the schematic diagram of the process is shown in FIG. Figure 1 shown.

[0039] The "transition metals" mentioned herein include nickel, cobalt, manganese and the like.

[0040] Example 1

[0041] This embodiment protects a method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process.

[0042] The method of this embodiment specifically includes the following steps:

[0043] (1) Mechanically grinding the inner surface of a discarded sagger used to produce lithium cobalt oxide positive electrode materials to a depth of about 3 mm, and collecting the resulting powder;

[0044] (2) 10% sulfuric acid is added at a ratio of 10:1 between liquid and solid, and the mixture is stirred and leached at 80°C for 2 hours. The solid and liquid are separated, and the leached residue is washed. The washing water and the leaching liquid are then combined.

[0045] (3) For the leachate, the cobalt ion concentration in the leachate was detected to be about 2.8 g / L. After removing most of the water by rotary evaporation, the cobalt ion concentration was 28 g / L. 2 g / L of cobalt ions (calculated as cobalt sulfate) was added to obtain a concentrated solution with a cobalt ion concentration of 30 g / L.

[0046] (4) After drying the leached residue, 7% kaolin and 2% glass powder were added, pulverized and mixed simultaneously, and then disc granulated to obtain particles with a diameter of 3-6 mm. The particles were calcined at 1000°C for 3 hours to obtain carrier particles with a certain strength.

[0047] (5) The carrier particles are immersed in the concentrated solution at a solid-liquid ratio of 1:4, vacuum impregnated for 1 hour, taken out and dried, calcined at 500° C. for 1 hour, and then the impregnation-drying-light calcination process is repeated twice to obtain catalyst precursor particles.

[0048] (6) The precursor particles are calcined at 800°C for 2 h to prepare catalyst particles.

[0049] After testing, the catalyst surface contains active components such as cobalt oxide and aluminum cobalt spinel. In a fixed bed, the catalyst can continuously catalyze potassium permonosulfate (PMS) to produce free radicals to achieve long-term degradation of sodium dodecylbenzene sulfonate solution (concentration of 50 mg / L). M is defined as the ratio of the mass of treated wastewater to the mass of the catalyst used. When M is 100, the degradation rate is 83%. When M is 1000, it still maintains a degradation rate of 45%, with excellent long-term stability.

[0050] Example 2

[0051] This embodiment protects a method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process.

[0052] The method of this embodiment specifically includes the following steps:

[0053] (1) Mechanically grinding the inner surface of a discarded sagger used to produce lithium manganese oxide positive electrode materials to a depth of about 2 mm, and collecting the generated powder;

[0054] (2) 12% sulfuric acid is added at a ratio of 8:1 between liquid and solid, and the mixture is stirred and leached at 70°C for 3 hours. The solid and liquid are separated, and the leached residue is washed. The washing water and the leaching liquid are then combined.

[0055] (3) The manganese ion concentration in the leachate was detected to be about 3.6 g / L. After removing most of the water by rotary evaporation, the manganese ion concentration was 36 g / L. 9 g / L of manganese ions (calculated as manganese sulfate) was added to obtain a concentrated solution with a manganese ion concentration of 45 g / L.

[0056] (4) After drying the leached residue, 8% montmorillonite and 2% fly ash were added, pulverized and mixed simultaneously, and then granulated by extrusion to obtain cylindrical particles with a diameter of 3-5 mm and a length of 1-2 cm. The particles were calcined at 800°C for 2 h to obtain carrier particles with a certain strength.

[0057] (5) The carrier particles are immersed in the concentrated solution at a solid-liquid ratio of 1:5, vacuum impregnated for 2 hours, taken out and dried, calcined at 600° C. for 1 hour, and then the impregnation-drying-light calcination process is repeated 3 times to obtain catalyst precursor particles.

[0058] (6) The precursor particles were calcined at 1000°C for 1.5 h to prepare catalyst particles.

[0059] After testing, the catalyst surface contains active components such as manganese oxide and manganese aluminum spinel. In a fixed bed, the catalyst can continuously catalyze potassium permonosulfate (PMS) to produce free radicals to achieve long-term degradation of rhodamine B dye (concentration of 20 mg / L). M is defined as the ratio of the mass of treated wastewater to the mass of the catalyst used. When M is 100, the degradation rate is 90%. When M is 1000, it still maintains a degradation rate of 75%, with excellent long-term stability.

[0060] Example 3

[0061] This embodiment protects a method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process.

[0062] The method of this embodiment specifically includes the following steps:

[0063] (1) Mechanically grinding the inner surface of the discarded sagger used to produce the ternary cathode material to a depth of about 4 mm, and collecting the generated powder;

[0064] (2) 10% sulfuric acid is added at a ratio of 12:1 between liquid and solid, and the mixture is leached at 95°C for 3 hours with stirring. The solid and liquid are separated, and the leached residue is washed. The washing water and the leaching liquid are then combined.

[0065] (3) For the leachate, the concentrations of nickel, cobalt, and manganese ions in the leachate were detected to be 2.1 g / L, 1.3 g / L, and 0.9 g / L, respectively, totaling 4.3 g / L. After removing most of the water by rotary evaporation, the concentration of nickel, cobalt, and manganese ions was 43 g / L, and 5 g / L of nickel ions (calculated as nickel sulfate), 7 g / L of cobalt ions (calculated as cobalt sulfate), and 10 g / L of manganese ions (calculated as manganese sulfate) were added to obtain a concentrated solution with a total nickel, cobalt, and manganese ion concentration of 65 g / L.

[0066] (4) After drying the leached residue, 7% kaolin and 3% feldspar were added, pulverized and mixed simultaneously, and then granulated by disc granulation to obtain particles with a diameter of 2-5 mm. The particles were calcined at 900°C for 2 h to obtain carrier particles with a certain strength.

[0067] (5) The carrier particles were immersed in the concentrated solution at a solid-liquid ratio of 1:6, vacuum impregnated for 1.5 hours, taken out and dried, calcined at 700°C for 1 hour, and then the impregnation-drying-light calcination process was repeated 4 times to obtain catalyst precursor particles.

[0068] (6) The precursor particles were calcined at 950°C for 2.5 h to prepare catalyst particles.

[0069] After testing, the catalyst surface contains active components such as nickel oxide, cobalt oxide, manganese oxide, aluminum cobalt spinel, nickel aluminum spinel, manganese aluminum spinel, etc. In a fixed bed, the catalyst can continuously catalyze potassium permonosulfate (PMS) to produce free radicals to achieve long-term degradation of sodium stearate solution (concentration of 30 mg / L). M is defined as the ratio of the mass of treated wastewater to the mass of the catalyst used. When M is 100, the degradation rate is 88%. When M is 1000, it still maintains a degradation rate of 61%, with excellent long-term stability.

[0070] Comparative Example 1

[0071] This comparative example protects a method for preparing a catalyst from discarded saggers in a lithium battery positive electrode material production process.

[0072] The method of this comparative example specifically comprises the following steps:

[0073] (1) crushing and grinding the discarded saggers for producing lithium cobalt oxide positive electrode materials, and collecting the ground powder;

[0074] (2) 10% sulfuric acid is added at a ratio of 10:1 between liquid and solid, and the mixture is stirred and leached at 80°C for 2 hours. The solid and liquid are separated, and the leached residue is washed. The washing water and the leaching liquid are then combined.

[0075] (3) The cobalt ion concentration of the leachate was detected to be about 0.22 g / L. After removing most of the water by rotary evaporation, the cobalt ion concentration was 2.2 g / L. 27.8 g / L of cobalt ions (calculated as cobalt sulfate) was added to obtain a concentrated solution with a cobalt ion concentration of 30 g / L.

[0076] (4) After drying the leached residue, 7% kaolin and 2% glass powder were added, pulverized and mixed simultaneously, and then disc granulated to obtain particles with a diameter of 3 to 6 mm. The particles were calcined at 1000°C for 3 hours to obtain carrier particles with a certain strength.

[0077] (5) The carrier particles are immersed in the concentrated solution at a solid-liquid ratio of 1:4, vacuum impregnated for 1 hour, taken out and dried, calcined at 500° C. for 1 hour, and then the impregnation-drying-light calcination process is repeated twice to obtain catalyst precursor particles.

[0078] (6) The precursor particles are calcined at 800°C for 2 h to prepare catalyst particles.

[0079] After testing, the catalyst surface contains active components such as cobalt oxide and aluminum cobalt spinel. In a fixed bed, the catalyst can continuously catalyze potassium permonosulfate (PMS) to produce free radicals to achieve long-term degradation of sodium dodecylbenzene sulfonate solution (concentration of 50 mg / L). M is defined as the ratio of the mass of treated wastewater to the mass of the catalyst used. When M is 100, the degradation rate is 79%. When M is 1000, it still maintains a degradation rate of 46%. The long-term stability is excellent, but the catalyst preparation cost is high.

[0080] Comparative Example 2

[0081] This comparative example protects a method for preparing a catalyst from discarded saggers in a lithium battery positive electrode material production process.

[0082] The method of this comparative example specifically comprises the following steps:

[0083] (1) Mechanically grinding the inner surface of a discarded sagger used to produce lithium cobalt oxide positive electrode materials to a depth of about 3 mm, and collecting the resulting powder;

[0084] (2) 10% sulfuric acid is added at a ratio of 10:1 between liquid and solid, and the mixture is stirred and leached at 80°C for 2 hours. The solid and liquid are separated, and the leached residue is washed. The washing water and the leaching liquid are then combined.

[0085] (3) For the leachate, the cobalt ion concentration in the leachate was detected to be about 2.8 g / L. After removing most of the water by rotary evaporation, the cobalt ion concentration was 28 g / L. 2 g / L of cobalt ions (calculated as cobalt sulfate) was added to obtain a concentrated solution with a cobalt ion concentration of 30 g / L.

[0086] (4) After drying the leached residue, 7% kaolin and 2% glass powder were added, pulverized and mixed simultaneously, and then disc granulated to obtain particles with a diameter of 3-6 mm. The particles were calcined at 1000°C for 3 hours to obtain carrier particles with a certain strength.

[0087] (5) The carrier particles were immersed in the concentrated solution at a solid-liquid ratio of 1:4, vacuum impregnated for 1 hour, taken out and dried, and calcined at 800° C. for 2 hours to prepare catalyst particles.

[0088] After testing, the catalyst surface contains active components such as cobalt oxide and aluminum cobalt spinel. In a fixed bed, the catalyst can continuously catalyze potassium permonosulfate (PMS) to produce free radicals to achieve long-term degradation of sodium dodecylbenzene sulfonate solution (concentration of 50 mg / L). M is defined as the ratio of the mass of treated wastewater to the mass of the catalyst used. When M is 100, the degradation rate is 59%, and when M is 1000, the degradation rate is only 26%.

[0089] Comparative Table of Degradation of Organic Matter by Advanced Oxidation Catalysts Prepared in Comparative Examples and Examples

[0090]

[0091] In Comparative Example 1, the entire waste sagger produced by the production of lithium cobalt oxide positive electrode materials is used as raw material, which is crushed, ground and then leached, resulting in the introduction of a large amount of inert components. Under the same solid-liquid ratio, the amount of acid used is greatly increased, and the content of transition metal ions in the leachate is very low, and a large amount of cobalt sulfate needs to be additionally added. Compared with Example 1, the amount of cobalt sulfate added in Comparative Example 1 is nearly 14 times that of Example 1, which greatly increases the preparation cost of the catalyst.

[0092] In Comparative Example 2, conventional one-step impregnation-calcination was used to prepare catalyst particles. Since the carrier has a limited adsorption capacity for transition metal elements in the leaching solution, a single impregnation-calcination will result in a low content of active components in the catalyst and poor catalytic performance. In Example 1, the impregnation-drying-light calcination process was repeated. After impregnation, the transition metal impregnated once was lightly calcined to generate small oxide precursor particles on the surface of the carrier, which increased the roughness and exposed surface area of ​​the carrier surface. On this basis, repeated impregnation can re-adsorb a large amount of transition metal elements. After repeated cycles, multiple layers of transition metal oxides and active components with spinel structures will be generated on the surface of the carrier, greatly improving the activity of the catalyst.

[0093] Combined with Comparative Example 1, the impregnation-drying-light calcination process should not be repeated more than 3 times. Too many repetitions will lead to the formation of a dense layer of transition metal oxide on the surface of the carrier, making it impossible for the active components in the inner layer to contact with the peroxymonosulfate, and the catalytic effect will be weakened.

[0094] Therefore, compared with the traditional scheme, the embodiment of the present invention uses less acid solution, has a high degree of transition metal enrichment in the leaching solution, a large loading amount of the active components of the catalyst, a low preparation cost of the catalyst, high pollutant degradation efficiency, and good long-term stability.

[0095] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an advanced oxidation catalyst from discarded saggers in the production process of lithium battery positive electrode materials, characterized in that: The steps include: S1: Mechanically grinding the surface of the waste sagger produced in the production process of lithium battery positive electrode materials to obtain ceramic powder containing transition metals; S2: acid leaching the ceramic powder containing transition metals to obtain a leaching solution and leaching residue containing transition metals; S3: concentrating the leaching solution containing transition metals to obtain a concentrated solution; S4: After the leached residue is dried, an auxiliary agent is added, mixed and formed into particles, and then dried and calcined to obtain a catalyst carrier; S5: placing the catalyst carrier into the concentrated solution, fully immersing and adsorbing it, taking it out, drying it and calcining it at low temperature, and then placing it into the concentrated solution again, repeating the immersion-drying-calcining process to obtain a catalyst precursor; S6: calcining the catalyst precursor to obtain an advanced oxidation catalyst.

2. The method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S1, the grinding depth of the inner surface of the discarded sagger does not exceed 5 mm.

3. The method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S2, the acid used for acid leaching is sulfuric acid with a mass concentration of 5% to 20%, a leaching liquid-solid ratio of 5:1 to 20:1, a leaching temperature of 20 to 100° C., and a leaching time of 0.5 to 5 hours.

4. The method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S3, the total concentration of transition metal ions in the concentrated solution is 10 to 100 g / L.

5. The method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S4, the auxiliary agent is at least one of kaolin, montmorillonite, feldspar, glass powder and fly ash, and the added amount does not exceed 10% of the dry weight of the leached residue.

6. The method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S4, the molding process includes granulation and extrusion; the calcination temperature is 800-1200° C., and the calcination time is 1-5 hours.

7. The method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S5, vacuum impregnation is performed for 0.5 to 2 hours; the light calcination temperature is 500 to 900° C., and the light calcination time is 0.5 to 3 hours; and the impregnation-drying-light calcination process is repeated 2 to 5 times.

8. The method for preparing an advanced oxidation catalyst from discarded saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S5, the concentrated solution after the cyclic immersion is completed can be returned to the acid leaching process as a mother solution.

9. The method for preparing an advanced oxidation catalyst from waste saggers in a lithium battery positive electrode material production process according to claim 1, characterized in that: In step S6, the calcination temperature is 600-1300° C., and the calcination time is 1-5 hours.

10. Use of the advanced oxidation catalyst prepared by the method according to any one of claims 1 to 9 in catalytic degradation of organic matter.

Citation Information

Patent Citations

  • A method for recycling and processing waste crucibles during the preparation of lithium cobalt oxide battery materials.

    CN109911946B

  • A comprehensive treatment method for waste refractory materials during the preparation of ternary cathode materials

    CN109913652B

  • Method for carrying out recovery treatment on waste saggar in lithium cobaltate positive electrode material preparation process

    CN109911909A

  • Comprehensive treatment method of waste refractory materials in ternary anode material preparation process

    CN109913652A

  • Method for preparing ozonolysis catalyst by utilizing waste LED lamp beads, ozonolysis catalyst prepared by method and application of ozonolysis catalyst

    CN112264037A

Cited By

  • Preparation method, product and application of NH3-SCR catalyst

    CN120132873A